Stance Expressions in Introduction of English Research Articles written by Cambodian Authors - Soeurn Chenda; Safnil Safnil; Syafryadin Syafryadin (Register Journal, 2022)
Stance Expression indicates feelings, certainty or uncertainty, and interests of the authors. As the increasing needs of the readers on significant findings from the introduction section of Research Articles, a study on Stance Expression of introduction section in the English research articles written by Cambodian authors has been conducted to employ crucial aims of the study: (1) examine stance expression types and the categories of each type; (2) compare the similarities and differences of stance expression types used in the introduction section of English RAs written by Cambodian authors published in local and international journals. Thirty research articles written by Cambodian authors published in local and international journals were used in this study. To fulfill these research objectives, the mixed-method research design was utilized in this study. All the four stance features, such as Hedges, Boosters, Attitude Markers, and Self-expression, proposed by Hyland (2005) were used as a Lexical analysis framework model in this study. The results revealed that four stance expression types were found in this study. The hedge was the most frequently employed among the other types of stances. There is a significantly different in terms of the frequencies of hedge used within both RA journals, but there is no for booster, attitude marker, and self-mention. Local Cambodian authors should follow the international authors as models in applying stance in their RAs.  A  comparison study of the stance expression and engagement between Cambodian and international authors in the introduction should be expanded more different articles from available journals.Keywords: English research article, introduction section, stance expression, local journals, international journals